Students’ Perceptions on YouTube as an Educational Tool in Teaching Cross-Cultural Communication - Fleșeriu, Cristina; Lifintsev, Denys; Amaral Jerónimo, Nuno; Tamulevičiūtė-Šekštelienė, Angelė (Pedagogika, 2023)
Contemporary globalisation requires a higher awareness of the hypercultural environment. YouTube is the most used digital social network and recent studies show youngsters use mainly online sources to understand the world. Global digital citizenship is a fundamental part of today's education. This paper focuses on the perceptions of higher education students about YouTube as a learning tool. Asked to assess an educational video about cross-cultural communication, students’ answers show they perceive it as a plus to their education.